The Political and Mental Aspects of Ukraine Integration with Europe - Hordiichuk, Olha; Dekert, Tomasz; Lysetska, Yulia (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
This research paper examines Ukraine’s path towards European integration. From the 10th to the 12th centuries, Ukraine – then known as Kyivan Rus’ – was a strong independent state, but due to internal conflicts and conquests, it became weakened and fell under the influence of other state entities. From the 17th century onwards, as a result of the Pereyaslav agreements (1654 and 1659) between the Cossacks and Moscow, Ukraine found itself increasingly under the sway of Russia, a situation that persisted until the collapse of the “prison of the peoples”, the Soviet Union. Despite Russian propaganda portraying Ukraine as an integral part of Russia for a long time due to shared history and culture, in reality, modern Ukraine and Russia are two different countries with distinct political systems, development trajectories, identities, mentalities, fundamental values, and traditions. Ukrainian society, though subjected to Sovietization during communist times and later targeted by political and propaganda actions from the Russian Federation, stands fundamentally opposed to the authoritarian Russian society and closer to the democratic European community. For centuries, Russian authorities sought to colonize and exploit Ukraine for their own interests, attempting to erase Ukrainian identity, language, traditions, and rewriting Ukrainian history, yet they failed to fully assimilate the Ukrainian people despite numerous manipulations and crimes against them. The European, Western development trajectory of Ukraine and its desire to break away from Russia’s sphere of influence is one of the main reasons for the current full-scale war. The greatest similarities between Ukraine and European states at the level of mentality include Ukrainian love for freedom, individualism, and desire for democracy, in contrast to Russian despotism and authoritarianism. These distinct features of the Ukrainian mentality have historically preserved and revived the Ukrainian nation, aiding in its further development and providing hope for its future not only geographically and economically but also mentally and spiritually.
Polityczne i mentalne aspekty integracji Ukrainy z Europą
Keywords: European integration processes; Europe; Ukraine; mentality; European civilization; Eurasian civilization; European value system; national identity